Evaluation of endophytic bacterial community isolated from different varieties of pineapple and their potential as biological control agents for controlling bacterial heart rot disease / Nur Amitum Abdul Kadir - Abdul Kadir, Nur Amitum (Faculty of Plantation and Agrotechnology, 2018)
Bacterial heart rot disease caused by Erwinia chrysanthemi, a pathogen that can attacks pineapple (Ananas comosus), an important tropical fruit crop in Malaysia. Currently, only one chemical pesticide which is Benomyl has been registered for controlling pineapple diseases. Heavily rely on this chemical should be reduced as the pathogen is able to develop pesticide resistance as been reported in many cases on other crops. This study was specifically carried out to access the diversity of endophytic bacteria that were isolated from healthy pineapple roots from different varieties which are MD2, Josapine and N36. The root samples were collected from FIMA, Ayer Hitam Johor. The roots were surface sterilised by following a common method for endophytic isolation and all the isolates were then analysed for their abundance and their potential as biological control agent against the bacterial pathogen in vitro. Results of this study showed, there were three species of endophytic bacteria were mostly found based on their appearances on media and microscopic characteristics observed under a light microscope. For in vitro screening, their potential against the pathogen were measured by the radius of inhibition zone that occur for each sample after 24 hour. The result indicated that there were two species are stronger to kill the pathogen and the varieties of pineapple plant were not affecting the existing of the species bacteria. Based on the research study, it can be concluded that some endophytic bacteria have potential to be further explored as biological control agent for controlling bacterial heart rot disease.